Cerebellum and nucleus caudatus asymmetry in major depressive disorder - Okumuş, Burak; Besenek, Mert; Sönmez, Doğancan; Beyazal Çeliker, Fatma; Hocaoglu, Cicek (Journal of Surgery and Medicine, 2022)
Background/Aim: The relationship between major depressive disorder (MDD) and specific brain regions was investigated using neuroimaging methods. Although the findings show structural hemispheric asymmetry, research has often focused on the specific brain region involved in MDD. This study aimed to investigate asymmetry in the brain regions of MDD patients for the first time with volBrain, which is a fully automated segmentation technique. Methods: Our study was designed as a case-control study. Structural asymmetry was evaluated using the current web-based fully automated segmentation algorithm, volBrain, that analyzes volumetric T1 axial magnetic resonance imaging data. Sixteen cases with MDD and 14 healthy controls were analyzed. For comparison of continuous data between binary groups, an independent T-test was used for data that follow a normal distribution and Mann–Whitney U (MWU) test was used for data that did not follow a normal distribution while categorical data were evaluated using Chi-square test (or Fisher’s exact test when needed). Results: There was no significant difference in terms of gender (χ2 [1, n = 30] = 0.117, P = 0.732), education level (2 [1, n = 30] = 0.002; P = 0.961] and marital status (P = 0.596, Fisher exact chi-square test). However, both groups were found to be similar in terms of age (P = 0.608, MWU test). Right/left nucleus caudatus volume ratios (P = 0.028, MWU test) and right/left cerebellum volume ratios were significantly smaller in the case group (P = 0.006, independent T-test). When the volumes of the right and left parts were compared, only the volume of the right globus pallidus was larger (statistically significant) in the case group (P = 0.008, independent T-test). Conclusion: In line with our hypothesis, our study supports the notion of cortico–striatal–pallidal–thalamic circuit abnormalities in current MDD research and found that some regions in this phase may contain structural asymmetry. In addition, this study contributed to the literature consisting of studies that have examined the relationship between cerebellum and MDD by adding that the cerebellum may show structural asymmetry. The results of our study suggest that research using volBrain may be beneficial to patients with MDD. Current web-based fully automatic segmentation algorithms can restrict both the rater-induced differences in manual segmentation applications and the differences that various segmentation algorithms can create. The challenge of multicenter research can be overcome by using web-based fully automated segmentation volumetry systems and data containing the same standardized magnetic resonance imaging (MRI) acquisition parameters because it is easy for clinicians around the world to access web-based fully automated segmentation volumetry systems. Research on fully automatic segmentation techniques might be the driving force behind fully understanding biological foundations of MDD in the future.